Factores de riesgo y su influencia en alergias respiratorias en niños de 0 a 5 años, Centro de Salud Enrique Ponce Luque, Babahoyo, Los Ríos. octubre 2018 - abril 2019 - Amaiquema Diaz, Evelin Mariela (2019)
Objective: To analyze the risk factors that influence respiratory allergies in children from 0 to 5 years old at the Enrique Ponce Luque Health Center, Babahoyo, los Ríos. October 2018 - April 2019 Methodology: We worked with a qualitative-quantitative, descriptive investigation that allowed us to know that one of the main risk factors that trigger respiratory allergies in patients from 0 to 5 years old. To obtain the data, we reviewed the clinical histories of the Enrique Ponce Luque Health Center, surveys of parents, once the data were obtained, we proceeded to work with the database, statistical data were included. Results: The average age of patients was from 2 months to 11 months, the male sex prevailed with 52%, the risk factors with the highest prevalence are due to the exposure of dust and chemicals with 33%, followed by 27% by Indoor pollution, 17% of the study population have a family history related to respiratory allergies. Conclusions: Therefore, it is important to inform the community of the risk factors that provoke respiratory allergies, finding a high index of 73% of allergic rhinitis, followed by 27% with asthma.